2015
DOI: 10.1038/ejcn.2015.68
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal development of obesity in the post-Fontan population

Abstract: During the first 5 years after Fontan palliation, there is a trend toward increasing percentages of OB and OW patients. In addition, there is a significant association between Hispanic ethnicity and being OW or OB before and after surgery. Further study is needed to determine whether OW/OB status is associated with worse health outcomes in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…Although our unmatched data and results from previous smaller studies suggest that obesity prevalence is lower in certain ACHD populations, several recent studies have found that individuals with complex CHD have an increased prevalence of obesity after the Fontan operation. [16][17][18] We found similar obesity rates between ACHD and control groups by using our greedy matching algorithm. This discrepancy highlights the importance of accounting for age and sex when defining these risk factors in the ACHD population.…”
Section: Discussionmentioning
confidence: 99%
“…Although our unmatched data and results from previous smaller studies suggest that obesity prevalence is lower in certain ACHD populations, several recent studies have found that individuals with complex CHD have an increased prevalence of obesity after the Fontan operation. [16][17][18] We found similar obesity rates between ACHD and control groups by using our greedy matching algorithm. This discrepancy highlights the importance of accounting for age and sex when defining these risk factors in the ACHD population.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have demonstrated lower rates of obesity in patients with single ventricles, obesity was present in 11% of pediatric and 17% of adult Fontan patients 55)56)57). Several recent studies have shown that patients post Fontan procedure have an increased prevalence of obesity 58)59)60). Association of obesity such as diastolic dysfunction and ventricular hypertrophy may complicate the management of ACHD patients who are already at risk for ventricular dysfunction, arrhythmias, and heart failure 61)62).…”
Section: Risk Factors For Coronary Artery Disease and Metabolic Syndrmentioning
confidence: 99%
“…As survival of children with serious illnesses such as cancer and heart disease has improved, lifestyle issues such as fitness, healthful eating and obesity have become long‐term concerns for them . Childhood cancer survivors (CCS) now face the same lifestyle issues as the general population as the habits they establish in their youth carry over into adulthood.…”
mentioning
confidence: 99%